Alcohol use and interpersonal violence: alcohol detected in homicide victims. - Goodman, R A (1986)
To characterize the relationship between alcohol use and homicide victimization, we used data from the Los Angeles City Police Department and the Los Angeles Medical Examiner's Office to study 4,950 victims of criminal homicides in Los Angeles in the period 1970-79. Alcohol was detected in the blood of 1,883 (46 per cent) of the 4,092 victims who were tested. In 30 per cent of those tested, the blood alcohol level was greater than or equal to 100 mg/100 ml, the level of legal intoxication in most states. Blood alcohol was present most commonly in victims who were male, young, and Latino, categories where rates have been increasing at an alarming pace. Alcohol was also detected most commonly in victims killed during weekends, when homicides occurred in bars or restaurants, when homicides resulted from physical fights or verbal arguments, when victims were friends or acquaintances of offenders, and when homicides resulted from stabbings. The evidence for alcohol use by homicide victims focuses attention on the need for controlled epidemiologic studies of the role played by alcohol as a risk factor in homicide and on the importance of considering situational variables in developing approaches to homicide prevention.